Exchange rates, capital flows and policy - Driver, Rebecca; Sinclair, P. J. N.; Thoenissen, C. (London ; New York : Routledge, 2005)
Combining thorough scholarship with illuminating real-world examples, this edited collection provides insights on the causes and consequences of movements in both exchange rates and external assets and has a strong focus on the policy implications of operating in an open economy, particularly the choice of exchange rate and monetary policy, exchange rate intervention and policies on capital mobility.
Includes bibliographical references and index.
rpm 08/09/2016
Loans
Keywords: Foreign exchange rates; Monetary policy; Capital movements